An Investigation into the Effects of Waste Glass Powder on the Condition of the Soil - Alwina Khatun Ansari,; Prathiba. P,; Preetha. S,; M. Nisha,; M. Saranya, (European Journal of Life Safety and Stability (2660-9630), 2023)
Soil stabilisation enhances the engineering properties of soils by alteration of the physical properties of the soil. It also increases the shear strength of soil, controls its shrink-swell properties and improves the load-bearing capacity of soils. Sustainable soil stabilisation relies heavily on recycling materials like old glass, plastic, and rubber. In particular, weak soils necessitate the use of effective soil stabilisation procedures to maintain sufficient stability. Soil stabilisation is one potential benefit of industrial wastes that are neither biodegradable nor compostable. Here, the soil has been stabilised with discarded glass powder, which is not biodegradable. Glass, being an inert material, cannot be broken down by natural processes. Similarly, to how natural rock deteriorates, it loses its integrity over time. Because of its inert nature, it can be used to fortify a wide range of soil and road-building components. Several experiments, including Specific Gravity, Atterberg limits, Standard Proctor Test, California Bearing Test, and Unconfined Compression Test, were conducted with varying percentages of glass powder and the results are described.